DEVELOPMENT OF MICROCONTROLLER BASED AUTOMATIC POWER SWITCH WITH GENERATOR START AND STOP CONTROLS (FULafia Journal of Science and Technology, 2018)
The erratic nature of power supply and use of generators as alternative source of electricity in the developing countries like Nigeria has necessitated the need for a mechanism that switches power to a given load between two sources of supply.. This study was therefore initiated to focus on the design and implementation of an automated system that executes switching functions usually from public supply to generator and vice versa when mains supply is unavailable and when it is restored. The device consists of power supply unit for converting from alternating current (A.C.) to direct current (D.C.), logic circuit for detecting when mains power is restored, relay unit for performing power switch as well as control unit for starting and stopping a generator. It was observed that the device eliminates the stress and possible downtime associated with manual operation of a change over switch. The study recommends the device to be essential in hospitals, banks, government and private agencies where critical operations requiring constant availability of power are carried out.
Keywords: alternating current; display control; microcontroller; relay